Indonesia’s insurance industry: Financial conditions during and after covid-19 - Yuliadi, Dani; Fitranita, Vika (Proceeding International Conference on Accounting and Finance, 2024)
The purpose of this study is to look at the bankruptcy of the insurance industry in Indonesia using the Altman, Springate, Zmijewski, and Grover models. This study examines how Islamic and conventional insurance companies have differences in financial distress during and after the COVID-19 pandemic in Indonesia. This research uses data from insurance companies in Indonesia registered with the Financial Services Authority (OJK) between 2019 and 2022. This study used puposive sampling samples, data documentation and Difference Test. The results of this study show that there are differences in financial conditions between conventional and sharia insurance companies during and after Covid-19 using the Altman Z-score model, Springate model, and Zmijewski model. Meanwhile, there is no difference in financial condition between conventional and sharia insurance companies during and after Covid-19 using the Grover model